The Impact of Internal Control Components on the Financial Performance, in the Iraqi Banking Sector - HANOON, RAAD NASER; KHALID, AZAM ABDELHAKEEM; RAPANI, NOR HANANI AHAMAD; ALJAJAWY, TALAL MOHAMMED; AL- WAELI, ABBAS JUMAAH (The journal of contemporary issues in business and government, 2021)
The aim of this study was to investigate the impact between Internal Control Components (ICC) and the Financial Performance (FP) of the Iraqi banking sector. The selected components were control environment, control activity, risk assessment, information & communication, and monitoring. The theoretical framework in this study was based on the Agency theory. A quantitative approach using Structural Equation Modelling (SEM) was utilised as the main study design. The data was collected from a group of respondents comprising CFO, CEO, Accountants, Internal Auditors, and Audit Committee selected through non-random purposive sampling. The actual survey questionnaire was distributed to 365 respondents, and the data were analysed using SEM to determine the impact between Internal Control Components and Financial Performance. The study results indicated that the Internal Control Components have a significant impact on Financial Performance. The positive significant relation were control activity (β =0.311, p<0.05), followed by risk assessment (β =0.203, p< 0.05), monitoring (β=0.176, p<0.05), control environment (β=0.164, p<0.05) and information & communication (β=0.157, p<0.05). In conclusion, the control activity is the most dominant ICC factor that affects financial performance. The main implication of the study is that Iraqi banks should focus on the improvement of Internal Control Components to enhance financial performance.